2006
DOI: 10.1080/02664760600708590
|View full text |Cite
|
Sign up to set email alerts
|

CUSUM method in predicting regime shifts and its performance in different stock markets allowing for transaction fees

Abstract: Statistical Process Control (SPC) is a scientific approach to quality improvement in which data are collected and used as evidence of the performance of a process, organisation or set of equipment. One of the SPC techniques, the cumulative sum (CUSUM) method, first developed by E.S. Page (1961), uses a series of cumulative sums of sample data for online process control. This paper reviews CUSUM techniques applied to financial markets in several different ways. The performance of the CUSUM method in predicting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The CUSUM method is considered particularly useful for identification of regime shifts, as well as small and sustained changes or slow fluctuations in the mean values, see e.g. (Yi et al, 2006, and references therein).…”
Section: Interannual and Interdecadal Variabilitymentioning
confidence: 99%
“…The CUSUM method is considered particularly useful for identification of regime shifts, as well as small and sustained changes or slow fluctuations in the mean values, see e.g. (Yi et al, 2006, and references therein).…”
Section: Interannual and Interdecadal Variabilitymentioning
confidence: 99%
“…Yi et al 46 applied CUSUM techniques in predicting regime shifts in stock market indices but in contrast with Lam and Yam, 45 they take into account transaction fees. The same CUSUM technique is used in 30 different stock markets and its performance is compared.…”
Section: Control Charts and Stock Marketsmentioning
confidence: 99%
“…The result of taking transaction fees into consideration is the deterioration of the performance of the CUSUM procedures. Yi et al 46 concluded that if transaction fees are included they find no acceptable values of k and h . In this situation, the performance of the CUSUM procedure is not so good as when the transaction fees are very small or excluded.…”
Section: Control Charts and Stock Marketsmentioning
confidence: 99%
“…Over decades, many new charts and their applications have been proposed and studied by SPC practitioners and researchers in engineering, management and statistics (Zeifman and Ingman 2005, Shu et al 2007, Jarrett and Pan 2007, Messaoud et al 2008, Shu et al 2008, Riaz and Does 2008. Among all the charts, the X (or X) chart and CUSUM chart are used most widely in industry and have attracted great research effort (Luceño and Puig-Pey 2002, Yi et al 2006, Liu et al 2006.…”
Section: Introductionmentioning
confidence: 99%